PENGARUH PEMBERIAN LIMBAH CAIR PRODUKSI TEMPE TERHADAP HASIL DAN DAYA TAHAN JAMUR MERANG (Volvariella volvaceae) - Apriyandi, Desi; Maryani, Yekti; Darini, Maria Theresia (Universitas Sarjanawiyata Tamansiswa, 2018)
This study aims to determine the effect of soy bean fermented liquid wasteas a growth supplement to growth, yield and durability of straw mushroom. Theresearch was conducted in Kepuhan village, Argorejo, Sedayu, Bantul, altitude 88m above sea level (dpl), regosol soil type, with soil pH 5.5-6,7, average temperatureis 26-320C, and rainfall ie 1,654.00 mm / th.The research was arranged in 1Completely Randomized Design (RAL) with 3 replications. The application oftempe waste on the was consists of 5 levels concentrations of 0%, 25%, 50%, 75%and 100%. The variables observed included the number of primordia, fruit bodydiameter, fruit body length, fresh weight of fruit body, weight of mushroom perharvest, total weight of harvest, total number of mushroom per harvest, aroma andtexture or hardness of straw mushroom. Analyze varians significant and continuedDuncan’s Multiple Range Test (DMRT) at 5% real level. The results show that thereis a real effect ofapplication of soy bean fermented liquid waste yield and durabilityof mushroom.